Efficient Synthesis of New Fluorinated β-Amino Acid Enantiomers through Lipase-Catalyzed Hydrolysis - Sayeh Shahmohammadi; Ferenc Fülöp; Enikő Forró (Molecules, 2020)
An efficient and novel enzymatic method has been developed for the synthesis of β-fluorophenyl-substituted β-amino acid enantiomers through lipase PSIM (Burkholderia cepasia) catalyzed hydrolysis of racemic β-amino carboxylic ester hydrochloride salts 3a–e in iPr2O at 45 °C in the presence of Et3N and H2O. Adequate analytical methods were developed for the enantio-separation of racemic β-amino carboxylic ester hydrochlorides 3a–e and β-amino acids 2a–e. Preparative-scale resolutions furnished unreacted amino esters (R)-4a–e and product amino acids (S)-5a–e with excellent ee values (≥99%) and good chemical yields (>48%).